Pelatihan Pengelolaan Media Sosial sebagai Upaya Penguatan Cultural Destionation Branding Desa Wisata Menari Tanon Kabupaten Semarang - Paranti, Lesa; Jazuli, Muhammad; Prameswari, Nadia Sigi; Wiyoso, Joko; Farkhatunnisa, Alif; Latifah, Ani Nur Auliyatun (Universitas Negeri Semarang, 2024)
The potential and uniqueness of Menari Village as a tourist village in Semarang Regency needs to be introduced to the wider community. Based on the survey that was carried out, the community service found problems that needed to be resolved, including 1) Menari Tanon Village already has one social media (Instagram) but it has not been managed optimally; 2) lack of human resource capabilities in terms of understanding and skills in creating content that carries local cultural themes and social media management. The aims of this service include: 1) improving social media management; 2) increasing human resource capabilities and forming cadres. One solution offered to this problem is providing training on content and social media management. The approach used in this service activity is Participatory Rural Appraisal (PRA) which takes the form of a training and mentoring method. The stages carried out in this service include 1) FGD with Pokdarwis, 2) training and assistance in social media management. The training activity involved 17 participants who were the young generation of Tanon Hamlet. The results of the training indicate increased understanding and ability to create content as well as manage social media and create. After the training is related to techniques for creating content on social media with activity output in the form of creative content videos. Next, assistance is provided with social media management by forming a social media team and creating a posting schedule